2016
DOI: 10.1016/j.adro.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcomes between SBRT, yttrium-90 radioembolization, transarterial chemoembolization, and radiofrequency ablation as bridge to transplant for hepatocellular carcinoma

Abstract: PurposeTo evaluate and compare outcome of stereotactic body radiation therapy (SBRT), yttrium-90 radioembolization, radiofrequency ablation (RFA), or transarterial chemoembolization (TACE) as bridge to liver transplant (LT) in patients with hepatocellular carcinoma.Methods and materialsWe retrospectively reviewed patients treated at our institution with SBRT, TACE, RFA, or yttrium-90 as bridge to LT between 2006 and 2013. We analyzed radiologic and pathologic response and rate of failure after bridge therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 34 publications
(28 reference statements)
2
67
0
Order By: Relevance
“…Abdominal compression with 4D-CT have also been used to reduce respiratory motion 19,21,50,52 as has respiratory gating 29,32,41 and intra-fraction tracking of peri-tumoral implanted fiducials 22,30,34,42,48 or external surface markers 20,22,30,43,48 (which requires daily imaging to ensure the adopted breathing model remains satisfactory). Free breathing with 4D-CT, with individualised margins to account for respiration, have also been employed 23 .…”
Section: Respiratory Motion Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdominal compression with 4D-CT have also been used to reduce respiratory motion 19,21,50,52 as has respiratory gating 29,32,41 and intra-fraction tracking of peri-tumoral implanted fiducials 22,30,34,42,48 or external surface markers 20,22,30,43,48 (which requires daily imaging to ensure the adopted breathing model remains satisfactory). Free breathing with 4D-CT, with individualised margins to account for respiration, have also been employed 23 .…”
Section: Respiratory Motion Managementmentioning
confidence: 99%
“…SBRT may help reduce this: following SBRT used as a bridging therapy, 63-100% of patients are reported to proceed to transplant, with low rates of toxicity, and with complete and partial pathological responses reported in 14-29% and 23-64% of lesions respectively [39][40][41][42][43] . Mohamed et al recently compared SBRT, TACE, RFA and yttrium-90 microspheres as bridge to transplant therapies in a retrospective series of 60 patients 43 . Mean pathological necrosis was not significantly different between modalities, and toxicities were lowest for SBRT and yttrium-90.…”
Section: Sbrt As a Bridge To Transplantmentioning
confidence: 99%
“…A retrospective review of 10 patients who received HIGRT and then underwent liver transplantation demonstrated a pathologic complete response (pCR) in 3 of 11 tumors (27%), and the remaining 8 tumors appeared decreased or stable in size. 76 Long-term outcomes for 312 patients who received bridging therapies of HIGRT, TACE, or RFA and then ultimately underwent transplantation indicated no significant differences in actuarial survival or survival from the time to transplantation at 1, 3, or 5 years based on treatment modality. 74 Another study of 38 patients who received HIGRT and then underwent transplantation reported a pathologic RR (complete and partial responses) of 68%, with a pCR achieved by 26% of patients.…”
Section: Rt As a Bridge To Transplantationmentioning
confidence: 93%
“…Grade 3 toxicity was noted in 6 patients who received TACE or RFA (there was no grade 3 toxicity in the HIGRT or radioembolization groups); pCR was noted in 29% with HIGRT, in 41% with TACE, in 60% with RFA, in 75% with radioembolization, and in 33% of patients who received multiple modalities. 76 Long-term outcomes for 312 patients who received bridging therapies of HIGRT, TACE, or RFA and then ultimately underwent transplantation indicated no significant differences in actuarial survival or survival from the time to transplantation at 1, 3, or 5 years based on treatment modality. 77 The 5-year survival rate after transplantation was 75% for HIGRT, 69% for TACE, and 73% for RFA.…”
Section: Rt As a Bridge To Transplantationmentioning
confidence: 93%
“…Radiographic local control rates exceed 85% (►Table 1). [84][85][86][87][88][89] In studies assessing for radiographic response only a few months after SBRT, response rates may be lower 90 but are likely underestimations as SBRT response can take up to 6 months or longer. 91 Pathologic response rates were variable, ranging from 37 to 70%.…”
Section: Bridge Therapy and Downstagingmentioning
confidence: 99%